Contaminated Sediments - Barceló, Damià (Springer, 2017)
When discussing the issue of contamination of the aquatic environment, water pollution is still the major aspect that has been regulated and extensively studied, but poor attention has been devoted to sediments. Sediments have been described as the sink or storage place and a source for contaminants entering river systems through various pathways. But bottom sediments have various functions in the environment, such as providing habitat for many aquatic organisms, and are an important component of aquatic ecosystems. This volume of the Handbook deals with various aspects of sediment contamination such as the fate and behavior of persistent organic pollutants, the application of sediment toxicity identification evaluation (TIE) protocols, and the various ways to degrade toxic pollutants from sediments. Overall the book provides readers the fundamental knowledge needed to better understand the complex issue of contaminated sediments.